2016
DOI: 10.1177/0748233716671206
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency radiation (900 MHz)-induced DNA damage and cell cycle arrest in testicular germ cells in swiss albino mice

Abstract: Even though there are contradictory reports regarding the cellular and molecular changes induced by mobile phone emitted radiofrequency radiation (RFR), the possibility of any biological effect cannot be ruled out. In view of a widespread and extensive use of mobile phones, this study evaluates alterations in male germ cell transformation kinetics following RFR exposure and after recovery. Swiss albino mice were exposed to RFR (900 MHz) for 4 h and 8 h duration per day for 35 days. One group of animals was ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 35 publications
1
29
0
2
Order By: Relevance
“…Moreover, appearance of multinucleated giant cells in the lumen of STs of this group suggested opening up of the cytoplasmic bridges between progeny of each cell division and fusion of their cellular contents [44] . These giant cells have been reported repeatedly in previous studies following RF -EMWs exposure [35,43] and were assumed to be due to excessive apoptosis induced by OS via mitochondrial dysfunction [51] . During spermatogenesis, apoptosis in testicular germ cells is considered as a physiologic mechanism to limit the germ cell population to numbers that the Sertoli cells can support [52] .…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Moreover, appearance of multinucleated giant cells in the lumen of STs of this group suggested opening up of the cytoplasmic bridges between progeny of each cell division and fusion of their cellular contents [44] . These giant cells have been reported repeatedly in previous studies following RF -EMWs exposure [35,43] and were assumed to be due to excessive apoptosis induced by OS via mitochondrial dysfunction [51] . During spermatogenesis, apoptosis in testicular germ cells is considered as a physiologic mechanism to limit the germ cell population to numbers that the Sertoli cells can support [52] .…”
Section: Discussionsupporting
confidence: 56%
“…Exposure to EMF has adverse effects on the proliferation and differentiation of spermatogonia, which may be important in understanding the pathogenesis of EMFinduced male infertility [42,43] . Therefore, we used PCNA as a tool to assess spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in humans, Agarwal et al reported that the continuous use of mobile phones is associated with decreased motility, sperm concentration, morphology and viability [ 20 ]. The most significant studies on the effect of RF-EMF emitted from different sources (cell phones, microwave ovens, laptops, and Wi-Fi devices) on animal and human fertility pattern are summarized in Table 1 [ 21 37 ].…”
Section: Introduction: History and Sources Of Microwavesmentioning
confidence: 99%
“…Significant increase in DNA damage of both 4 & 8 h exposure. Pandey et al 2017 [ 21 ]. Sprague Dawley male rats, n = 8 900 MHz mobile phone frequency; 1 h/ day for 30 days; SAR 0.025 W/kg Significant increase in apoptosis and changes in the levels of SOD, GPx, CAT, LPO.…”
Section: Introduction: History and Sources Of Microwavesmentioning
confidence: 99%
“…It was estimated in 2014 that there were 6.9 billion cellular phone memberships globally which continues to increase with the development of new generation mobile communication systems such as 4 G-5G. Given the large number of cellular phone users, it is important to examine, understand and monitor the possible impacts of radiofrequency radiation (RFR) on public health [1]. Cellular phones with a communication basis emit radiofrequency and electromagnetic waves (EMW) in the 800 and 2200 MHz frequency range [2].…”
Section: Introductionmentioning
confidence: 99%